Evaluation of Bruton’s Tyrosine Kinase (BTK) inhibition with alternative doses of ibrutinib in subjects with Chronic Lymphocytic Leukemia (CLL) - Ouerdani, Aziz; Valenzuela, Belén; Treijtel, Nicoline; Haddish-Berhane, Nahor; Desphande, Sanjay; Srinivasan, Srimathi; Smith, Emma; Perez Ruixo, Juan José (Cancer chemotherapy and pharmacology, 2025)
Purpose To evaluate alternative ibrutinib dosing regimens that maintain Bruton’s tyrosine kinase (BTK) receptor occupancy over the entire dosing interval for CLL patients using a model-based approach. Methods Ibrutinib inhibits B-cell proliferation via irreversible binding of BTK. As IC 50 is not an appropriate parameter to describe the potency of the inhibition in the presence of a covalent binding inhibitor. A BTK covalent binding model was developed using k inact /K I as key parameter to account for covalent binding. The ibrutinib-BTK covalent binding model was used to describe the effect of daily doses of 140, 280, 420 and 560 mg on the proportion of subjects with more than 90% BTK inhibition at steady state trough concentrations. Predictive performance of the model was assessed using the available ibrutinib BTK inhibition data following QD dosing. Model-based predictions were used to identify the minimum ibrutinib QD dose that provides more than 90% inhibition in more than 90% of the subjects. Results The covalent binding model was able to describe the data and predicted that ibrutinib QD dose reduced from 420 mg to 280 mg or 140 mg may inhibit de novo synthetized BTK efficiently in a CLL population. Conclusion Using a model-based approach showed that reducing the ibrutinib dosing regimen to 280 mg QD or even 140 mg in case of adverse events could maintain BTK inhibition over the entire dosing interval.